Quantifying Tensile Properties of Bamboo Silicone Biocomposite using Yeoh Model - Nizam Hassan, Kamarul; Mahmud, Jamaluddin; P.P. Abdul Majeed, Anwar; Azman Yahya, Mohd (International Journal of Engineering and Technology, 2018)
The utilisation of bamboo has the potential of improving the properties of silicone. However, a thorough investigation has yet to be reported on the mechanical properties of bamboo silicone biocomposite. This study was carried out with the aim to quantify the tensile properties and assess the tensile behaviour of bamboo silicone biocomposite using Yeoh hyperelastic constitutive function. The specimens were prepared from the mix of bamboo particulate and pure silicone at various fibre composition ratio (0wt%, 1wt%, 3wt% and 5wt%) cured overnight at room temperature. A uniaxial tensile test was carried out by adopting the ASTM D412 testing standard. The Coefficient of Variation, CV, and the Coefficient of Determination, r2, were determined to assess the reliability of the experimental data and fitting model. The results of the determined Yeoh material constants for 5wt% specimen is found to be C1 = 12.0603Ã—10-3 MPa, C2 = 8.7353Ã—10-5 MPa and C3 = -11.6165Ã—10-8 MPa, compared to pure silicone (0wt%) C1 = 5.6087Ã—10-3 MPa, C2 = 8.6639Ã—10-5 MPa and C3 = -7.6510Ã—10-8 MPa. The results indicate that the bamboo fibre improves the stiffness of the silicone rubber by 115 percent. A low variance was exhibited by the experimental data with a CV value of less than 8 percent. The Yeoh Model demonstrated an excellent prediction of the elastic behaviour of bamboo silicone biocomposite with a fitting accuracy of more than 99.93 percent.Â Â